Mixed course of Fasciolosis and Paramphistomatosis in sheep in Uzbekistan - B. S. Salimov; H. E. Otaboev (Российский паразитологический журнал, 2020)
The purpose of the research to study the mixed course of sheep infection, caused by pathogens of fasciolosis and paraphistomatosis, in the conditions of Samarkand and Tashkent regions. Materials and methods. The research material was fallen and forcibly killed sheep from two regions of Uzbekistan, simultaneously infected by Fasciola gigantica and Paramphistomum spp. (Gastrothylax crumenifer, Calicophoron calicophorum). The animals' liver was subjected to complete helminthological dissection, followed by the presence of young immature in the parenchyma, and in the bile ducts – sexually mature fasciola. To detect pathogens of paramphistomatosis, we examined the scar and mesh, and, if necessary, the mucous membranes of the abomasum and the initial part of the small intestine. To kill the collected F. gigantica and complete bleeding with a Paramphistomum spp., they were kept in water for one and three to four days, respectively. After they took their natural form, their type, age and number were determined, and then fixed in Barbagallo fluid. If necessary, coprological studies of sheep and malacological studies of biotopes of freshwater mollusks, intermediate hosts of the studied trematodes, were carried out. Results and discussion. In recent years, cases of a mixed course in sheep fasciolosis (F. gigantica) and paramphistomatosis in farms of Uzbekistan have become more frequent. When opening the liver of the fallen sheep, up to 278 specimens were found immature F. gigantica and up to 3994 sp. G. crumenifer. In some farms, the death of individual owners' sheep from calicophorosis caused by C. calicophorum was observed with an intensity of infection of 592 sp. of C. calicophorum.